Remote Ischemic Perconditioning in Thrombolysed Stroke Patients: Randomized Study of Activating Endogenous Neuroprotection – Design and MRI Measurements. Issue 2 (February 2013) - Hougaard, K. D.; Hjort, N.; Zeidler, D.; Sørensen, L.; Nørgaard, A.; Thomsen, R. B.; Jonsdottir, K.; Mouridsen, K.; Hansen, T. M.; Cho, T-H.; Nielsen, T. T.; Bøtker, H. E.; et al.
Background: Intravenous administration of alteplase is the only approved treatment for acute ischemic stroke. Despite the effectiveness of this treatment, 50% of patients suffer chronic neurological disability, which may in part be caused by ischemia-reperfusion injury. Remote ischemic perconditioning, performed as a transient ischemic stimulus by blood-pressure cuff inflation to an extremity, has proven effective in attenuating ischemia-reperfusion injury in animal models of stroke. Remote ischemic perconditioning increases myocardial salvage in patients undergoing acute revascularization for acute myocardial infarction. To clarify whether a similar benefit can be obtained in patients undergoing thrombolysis for acute stroke, we included patients from June 2009 to January 2011. Aim and design: The aims of the study are: to estimate the effect of remote ischemic perconditioning as adjunctive therapy to intravenous alteplase of acute ischemic stroke within the 4½-h time window and to investigate the feasibility of remote ischemic perconditioning performed during transport to hospital in patients displaying symptoms of acute stroke. Patients are randomized to remote ischemic perconditioning in a single-blinded fashion during transportation to hospital. Only patients with magnetic resonance imaging-proven ischemic stroke, who subsequently are treated with intravenous alteplase, and in selected cases additional endovascular treatment, are finally included in the study. Study outcomes: Primary end-point is penumbral salvage. Penumbra is defined as hypoperfused yet viable tissue identified as the mismatch between perfusion-weighted imaging and diffusion-weighted imaging lesion on magnetic resonance imaging scans. Primary outcome is a mismatch volume not progressing to infarction on one-month follow-up T2 fluid attenuated inversion recovery. Secondary end-points include: infarct growth (expansion of the diffusion-weighted imaging lesion) from baseline to the 24-h and one-month follow-up examination. Infarct growth inside and outside the acute perfusion-weighted imaging–diffusion-weighted imaging mismatch zone is quantified by use of coregistration. Clinical outcome after three-months. The influence of physical activity (Physical Activity Scale for the Elderly score) on effect of remote ischemic perconditioning. Feasibility of remote ischemic perconditioning in acute stroke patients. Summary: This phase 3 trial is the first study in patients with acute ischemic stroke to evaluate the effect size of remote ischemic perconditioning as a pretreatment to intravenous alteplase, measured as penumbral salvage on multimodal magnetic resonance imaging and clinical outcome after three-months follow-up.